Recent Advances in the Treatment of Coronary In-Stent Restenosis - Luca Sartore; Mauro Gitto; Angelo Oliva; Ryota Kakizaki; Roxana Mehran; Lorenz Räber; Alessandro Spirito (Reviews in Cardiovascular Medicine)
In-stent restenosis (ISR) remains the predominant cause of stent failure and the most common indication for repeat revascularization. Despite technological advances in stent design, ISR continues to pose significant challenges, contributing to increased morbidity and mortality among patients undergoing percutaneous coronary interventions. In the last decade, intravascular imaging has emerged as an important method for identifying the mechanisms behind ISR and guiding its treatment. Treatment options for ISR have expanded to include balloon angioplasty, cutting or scoring balloons, intravascular lithotripsy, atheroablative devices, drug-eluting stents, drug-coated balloons, surgical revascularization, and intravascular brachytherapy. The aim of the current review is to describe the classification and mechanisms of ISR, provide a comprehensive and updated overview of the evidence supporting different treatment strategies, suggest a management algorithm, and present insights into future developments in the field.